Pengaruh volume gas argon terhadap kekuatan tarik pada pengelasan GTAW SUS 201 - Andhika Hendrawan Febrianto; Am Mufarrih (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
Gas Tungsten Arc Welding (GTAW) is an arc welding process that uses a non-melting electrode. The GTAW welding process is carried out by melting the filler rod onto the object to be welded. The GTAW process on stainless steel materials, especially the SUS 201 type, has not yet obtained optimum joint strength. Therefore, it is necessary to have a research study on the tensile strength of GTAW welding results on SUS 201. The purpose of this study is to determine the effect of argon gas volume on the tensile strength of GTAW welding joints of SUS 201 material. Using experimental methods and data analysis using ANOVA. The independent variable used was the volume of argon gas, there are 5, 10, and 15 l/minute with three replications and the dependent variable was tensile strength. The results of this study indicate that the volume of argon gas has a significant effect on the tensile strength of GTAW welded material SUS 201. The maximum tensile strength value of GTAW welded with 15 l/minute argon gas volume is 630.86 MPa and the lowest value is found at 5 l/minute argon gas volume of 499.46 MPa. The greater the volume of argon gas, the greater the tensile strength. From the observation of the microstructure it is known that the volume of argon gas is 5 l/minute, the ferrite microstructure is more dominant than perlite, so the minimum tensile strength is stated. Meanwhile, at the volume of argon gas 15 l/minute, the microstructure of perlite is more dominant than ferrite, so the maximum tensile strength is stated.